New Insights into Gastroretentive Dosage Forms in Delivery of Drugs - Mathur, Pooja; Jhawat, Vikas; Dutt, Rohit (Current Nanomedicine, 2021)
The oral drug delivery route is preferable to deliver the therapeutic agents because of the low cost, flexibility in dosage form, and easy administration of drugs responsible for a high range of patient compliance. GRDDS is also an oral route of drug delivery system to prolong gastric residence time, thereby achieving site-specific drug release in the upper GIT for local or systemic effect. Various strategies for developing systematic GRDDS include approaches with less density than stomach contents, systems with high density, swellable and expanding strategies, formulation of super porous hydrogels, gas generating systems, hydrodynamically balanced, raft forming approaches, floating drug delivery, and dual working systems. The massive challenge in developing systemic GRDDS is inter and intra-individual differences in gastric physiology. Despite so many formulation strategies, these systems might be associated with few benefits as well as drawbacks. Drawbacks with few approaches can be overthrown by formulating novel dual working systems such as a Mucoadhesive Floating Drug Delivery System (MFDDS). These systems can form an intimate contact of the formulation with the stomach's mucosal membrane and increase the dosage formulation's absorption at the target site. The present compilation aims to outline the stomach's physiological state, the ideal characteristics of drugs for GRDDS, key factors impacting GRDF efficacy, and gastroretentive formulation strategies that could become the critical processes in the pharmaceutical research for target drug delivery. It also explores various marketed products of GRDDS and future perspectives.
Keywords: sustained release